Faktor-Faktor Yang Mempengaruhi Kemiskinan di Pulau Sulawesi - Friska Mahmud; Fachrudin Zain Olilingo; Fitri Hadi Yulia Akib (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2020)
The research aims to find our the factors impacting poverty in Sulawesi Island, including unemployment, economic growth, and everage length of school. Data employed are secondary data from Statistics Indonesia from 2015 to 2019 in six provinces. Method used in this research is multiple linear regression analysis of panel data. The research finding indicates that unemployment impacsts poverty positively but insingnificantly, which denotes that every increase in unemployment rate does not always increase poverty rate in Sulawesi Island. Then, the economic growth impacts poverty negatively and significantly, which denotes that every increase in economic growth can reduce the poverty rate in Sulawesi Island. Lastly, the everage length of school impacth poverty negatively and significantly, which denotes that every increase in the everage length of school is followed by reducation in the poverty rate in Sulawesi Island.